Criteria For Selecting Surgical Treatment Of Patients With Vental Hernias And Obesity - Rakhmanov Kosim Erdanovich; Davlatov Salim Sulaimanovich; Abdurakhmanov Diyor Shukurillaevich; Abduraimov Zafarzhon Abduraimovich (Periodica Journal, 2022)
Obesity plays an important role in the occurrence of wound complications in the early postoperative period and relapses in subsequent hernia repair of postoperative ventral hernias. A comparative analysis of the surgical treatment of 82 patients with postoperative ventral hernias with obesity of varying degrees, using autoplasty and alloplasty to close the hernia gate using clinical and instrumental research methods, was carried out. Chevrel-Rath classification of ventral hernias was used for diagnosis, obesity was determined by body mass index. All patients underwent hernia repair in the traditional way. The control examination was carried out after 1, 6, 12 months. Statistical analysis was carried out using comparative rates of wound complications and hernia recurrence depending on the severity of obesity and the type of surgical intervention. The study found that overweight in patients with postoperative ventral hernias is an important factor in the development of postoperative wound complications in 17.1% of cases and in 6.1% of hernia recurrences. The frequency and likelihood of wound complications in the surgical treatment of postoperative ventral hernias is significantly higher in obesity of III and IV degrees, mainly after autoplasty of the hernia gate, while maintaining the risk of hernia recurrence in the long-term period after surgery.
Keywords: alloplasty; autoplasty; obesity; ventral hernia